Akhlak Remaja Masa Kini: Antara Media Sosial, Self-Branding, dan Keteladanan Nabi - Arina Manasikana; Mutiara Nabila; Zulista Sukma; Resti Yulastri (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This article aims to analyze the dynamics of today's youth morality, which is influenced by the intensity of social media, self-branding practices, and the weakening of internalized prophetic values in everyday life. This study also examines the role of family, school, and society in building an adaptive digital morality development ecosystem that can respond to the challenges of the modern era. The research method employed is library research, utilizing a descriptive-analytical approach. Data were obtained from books, national and international journals, and scientific articles relevant to the themes of adolescent morality, digital literacy, and values education in Islam. The analysis was conducted by examining the patterns, trends, and theoretical concepts that emerged from various sources. The results of the study show that social media has a significant influence on adolescent behavior and identity construction, especially through the culture of self-branding that encourages self-image orientation. The lack of prophetic role models strengthens adolescents' vulnerability to moral disorientation. The integration of digital literacy, understanding of adolescent psychology, and Islamic values is are important strategy in digital ethics development. Additionally, the synergy between family, school, and community has proven to be a key factor in creating an environment that supports the development of an adolescent character that is responsible and aligned with Islamic values. These findings emphasize that character building based on the era in   Keywords: youth ethics, social media, self-branding, prophetic values, digital literacy